Female reproduction bears no survival cost in captivity for gray mouse lemurs. Issue 11 (18th May 2019) - Landes, Julie; Henry, Pierre‐Yves; Hardy, Isabelle; Perret, Martine; Pavard, Samuel
Abstract: The survival cost of reproduction has been revealed in many free‐ranging vertebrates. However, recent studies on captive populations failed to detect this cost. Theoretically, this lack of survival/reproduction trade‐off is expected when resources are not limiting, but these studies may have failed to detect the cost, as they may not have fully accounted for potential confounding effects, in particular interindividual heterogeneity. Here, we investigated the effects of current and past reproductive effort on later survival in captive females of a small primate, the gray mouse lemur. Survival analyses showed no cost of reproduction in females; and the pattern was even in the opposite direction: the higher the reproductive effort, the higher the chances of survival until the next reproductive event. These conclusions hold even while accounting for interindividual heterogeneity. In agreement with aforementioned studies on captive vertebrates, these results remind us that reproduction is expected to be traded against body maintenance and the survival prospect only when resources are so limiting that they induce an allocation trade‐off. Thus, the cost of reproduction has a major extrinsic component driven by environmental conditions. Abstract : We investigated the effect of reproductive effort on later survival for female gray mouse lemurs in captive conditions. Thanks to detailed individual monitoring, we were able to control, at levels rarely reached, for interindividual heterogeneity, as well as cohort and period effects. However, we did not detect any survival cost of reproduction, but rather a positive effect or reproductive effort on survival the next years.